Penerapan Strategi Inkuiri Untuk Meningkatkan Kemampuan Saintifik Siswa Dalam Pembelajaran Biologi SMA: (Application of Inquiry Strategy to Improve Students' Scientific Ability in High School Biology Learning) - Nurlailatus Safitri; Putri Prisilia Saragih; Thahara Sumayya Zukarnain; Pinkan Deviana Khairunnisa; Indayana Febriani Tanjung (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The purpose of this research is to improve students' scientific ability, by applying inquiry learning strategies in biology learning. This research is in the form of classroom action research with qualitative data analysis. Based on observational data on students' scientific abilities, it is known that in the first cycle for aspects A (asking) and B (observing) all students obtained the